Industrial wastes as substrates for synthesis of surfactants with antiadhesive activity by Rhodococcus erythropolis IMV Ac-5017 - Pirog, Tatiana; Kliuchka, Igor; Kliuchka (Nykytyuk), Lilia (My University, 2022)
Microbial surfactants can affect the degree of microorganism’s adhesion to different surfaces and lead to biodegradation of the already formed biofilms. They are also non-toxic to the environment. These properties allow to use the microbial surfactants in medicine and food industry.
Keywords: surfactants; Rhodococcus erythropolis; waste; biofilm destruction; поверхнево-активні речовини; адгезія; біоплівки; кафедра біотехнології і мікробіології